Citrullinated Antigens with Multiple Citrulline Similar Motif in the Diagnosis of Rheumatoid Arthritis: A Preliminary Single-Center Study - Zhu Chen; Weiting Fang; Yi Qin; Yin-Zhao Jin; Xiang Yang; Jianrong Lou (Journal of Immunology Research)
The presence of anti-citrullinated protein antibodies (ACPAs) in the serum is one of the immunological features of rheumatoid arthritis (RA). Anti-cyclic citrullinated peptide (CCP) assay has been widely used in clinic for the diagnosis of RA. However, up to 40% of RA patients are anti-CCP negative and the diagnostic sensitivity in this population needs to be improved for better clinical management. In this study, peptides with Multiple Citrulline Similar Motif (MCSM) were synthesized and a new ELISA system, which we called RA_CP, was developed to detect citrullinated antigens with MCSM present in the serum. 106 RA,48 other arthritis patients and 41 sex- and age-matched healthy controls (HCs) were included in this study. Patients with RA have a significantly higher amount of citrullinated antigens with MCSM than other arthritis patients and HCs. RA patients with positive anti-CCP are also MCSM positive, whereas 75% anti-CCP negative patients are positive for MCSM. The diagnostic sensitivity for anti-CCP and MCSM was 81.1% and 95.3%, while the specificity was 100% and 94.4%, respectively. ROC curve analyses showed that the area under the curve (AUC) values were 0.906 (95% CI: 0.860-0.951) for anti-CCP and 0.948 (95% CI: 0.912-0.985) for MCSM while the combination of MCSM and anti-CCP test has the highest AUC (0.971, 95% CI: 0.946–0.996). Our results suggest that detection of citrullinated antigens with MCSM has improved sensitivity compared with anti-CCP assay and could serve as a biomarker in diagnosis of RA patients.